Insight into watershed hydrodynamics using silica, sulfate, and tritium: Source aquifers and water age in a mountain river. (September 2021) - Campbell, Éowyn M.S.; Lagasca, Patrick A.; Stanic, Sofija; Zhang, Yuan; Ryan, M. Cathryn
Abstract: A clear concept of the recharge pathways for surface flow in mountain rivers is important for understanding the effects of climate change on streamflow in mountain block hydrology. In a mountain river in Alberta, Canada, three subsurface end-member sources were identified using silica, sulfate, and the isotopic composition of sulfate: interflow (water that has not undergone significant rock-water interaction), and groundwater derived from two types of hydrogeologic units (carbonate and siliciclastic fractured rock aquifers). A three end-member mixing model was used to determine their relative contributions to river discharge and infer relative groundwater ages using silica dissolution kinetics and tritium. In the three years of sampling, proportional contributions from subsurface end-members varied up to 25% within a given year while mean contributions between years varied as much as 19%. Interflow is the dominant source for the majority of the study period, contributing ~50% of river discharge during spring melt and 40–60% over the rest of the season. Siliciclastic and carbonate aquifer contributions varied interannually and seasonally. Although carbonate rocks comprise the majority of the watershed area, siliciclastic rocks contribute nearly equally to annual streamflow (~30% each), suggesting that siliciclastic aquifers transmit more water. Silica- and tritium-based ages suggest residence times on the order of <5–10 years. The combination of short residence times and significant variability in streamflow provenance suggest streamflow in this river will be rapidly affected by climatic change. Highlights: Silica, sulfate, and sulfate isotopes are used to identify three source aquifers. Streamflow has groundwater residence time of <5–10 years (from silica and tritium). Streamflow responds rapidly to seasonal and storm inputs and is therefore vulnerable to climatic change.